PENGARUH FUNGSI KEPEMIMPINAN TERHADAP KINERJA PEGAWAI PADA DINAS PENDIDIKAN KOTA AMBON - Eline Octoviana Hutubessy (Jurnal Administrasi Terapan, 2022)
To develop an organization so that it can run well and with direction, good performance is also needed from a leader to his subordinates so that they want to work properly and correctly in accordance with the goals that are expected together. Performance is a measure that includes effectiveness in achieving goals and efficiency which is the the ratio of effective output to input required to achieve that goal. According to the author's observations, this also happened to employees in the Administration section, where initially the employee's performance was so good and good, but the lack of attention from the leadership towards the work carried out by employees, and the lack of guidance from the leadership to each employee resulted in the resulting performance being less so good.Lack of attention and guidance from leaders to employees so that the performance of employees of the Ambon City Education Office, especially the administration section, has decreased as the services provided to the community have become less good. The analysis technique used by the author in solving this writer is simple linear regression, which is about the dependence of one dependent (bound) variable with one or more independent variables (explanatory/independent variables), with the aim of estimating or predicting the population average or value the average dependent variable based on the known value of the independent variable. Based on the results of data analysis using simple linear regression analysis, it is known that there is a positive relationship between leadership function and performance. This means that every increase in the leadership function will increase employee performance at the Ambon City Education Office.This should be taken into consideration for the Ambon City Education Office Leaders to always pay attention to employees in order to improve Employee Performance Keywords: Leadership, Performance